Effectiveness of Biofeedback Therapy on Quality of Life in Patients with Dyssynergic Defecation Disorder - Özkütük, Nilay; Eşer, İsmet; Bor, Serhat (Turkish Journal of Gastroenterology, 2021)
Background: The first option to be considered in the treatment of functional defecation disorder is to correct the dyssynergia. However, limited studies exist to show the effectiveness of biofeedback.Objective: We evaluated the effect of biofeedback on the severity of constipation, quality of life, and anorectal manometry in patients with dyssynergic defecation in which the biofeedback method was applied.Methods: Effectiveness of biofeedback method on the quality of life of 24 dyssynergic defecation patients according to Rome III criteria after clinical and balloon expulsion tests (BETs) and colonic transit time was measured. Data were collected with patient identification form, Bristol Stool Chart, Constipation Quality of Life Scale forms, Visual Analogue Scale, diaphragmatic breathing exercises form, constipation diary, and constipation biofeedback monitoring form. Dyssnergic defecation cases received 6-week biofeedback training. For the same timeframe, the control group had a catheter into the rectum without any intervention.Results: Constipation severity was reduced in both groups before biofeedback to post-biofeedback (P < .05). Anal canal pressure, BET, colonic transit time, and quality of life significantly improved in biofeedback patients compared with controls.Conclusions: Biofeedback has a favorable effect on therapy and quality of life in dyssynergic defecation cases.